Enhancing Qur'anic Literacy Among The Community of Sioban Village Mentawai Islands Through The Service Learning Method - Alim, Muhammad Nurul; Jefri Adiminoto; Tio Gunawan; Laode Muhammad Raudhatul Jannah; Ashari Erlangga; Randy Putra Lopolisa; Ahmad Sholihin; Muhhammad Faujan (ASSUNNAH PRESS, 2025)
The high rates of illiteracy, both in Latin script and in the Arabic script of the Qur'an, pose a major challenge to strengthening religious literacy within minority Muslim communities, particularly in remote areas such as Sioban Village in the Mentawai Islands. This community service project aims to enhance Qur'anic reading skills among illiterate community members through the application of a community-based Service Learning model, utilizing the talaqqi-tahsin approach, contextual learning, and the reinforcement of religious character. The methods employed included intensive training sessions, experience-based repetition, and the active involvement of local leaders and families. The results of the program indicate that approximately 40% of participants were able to independently read basic Qur'anic text, alongside a significant increase in self-confidence and religious participation. These findings suggest that a community- and person-centered approach is effective in addressing religious literacy challenges in marginalized communities. It is hoped that this program can serve as an implementable model for Qur'anic illiteracy eradication initiatives in other remote areas with similar characteristics.